Intramedullary nailing of extra-articular distal tibial fractures: biomechanical evaluation of stability immediately after fixation in a synthetic bone model. (1st February 2021) - Hadeed, Michael M.; Prakash, Hans; Yarboro, Seth R.; Weiss, David B.
Abstract : Aims: The aim of this study was to determine the immediate post-fixation stability of a distal tibial fracture fixed with an intramedullary nail using a biomechanical model. This was used as a surrogate for immediate weight-bearing postoperatively. The goal was to help inform postoperative protocols. Methods: A biomechanical model of distal metaphyseal tibial fractures was created using a fourth-generation composite bone model. Three fracture patterns were tested: spiral, oblique, and multifragmented. Each fracture extended to within 4 cm to 5 cm of the plafond. The models were nearly-anatomically reduced and stabilized with an intramedullary nail and three distal locking screws. Cyclic loading was performed to simulate normal gait. Loading was completed in compression at 3, 000 N at 1 Hz for a total of 70, 000 cycles. Displacement (shortening, coronal and sagittal angulation) was measured at regular intervals. Results: The spiral and oblique fracture patterns withstood simulated weight-bearing with minimal displacement. The multifragmented model had early implant failure with breaking of the distal locking screws. The spiral fracture model shortened by a mean of 0.3 mm (SD 0.2), and developed a mean coronal angulation of 2.0° (SD 1.9°) and a mean sagittal angulation of 1.2° (SD 1.1°). On average, 88% of the shortening, 74% of the change in coronal alignment, and 75% of the change in sagittal alignment occurred in the first 2, 500 cycles. No late acceleration of displacement was noted. The oblique fracture model shortened by a mean of 0.2 mm (SD 0.1) and developed a mean coronal angulation of 2.4° (SD 1.6°) and a mean sagittal angulation of 2.6° (SD 1.4°). On average, 44% of the shortening, 39% of the change in coronal alignment, and 79% of the change in sagittal alignment occurred in the first 2, 500 cycles. No late acceleration of displacement was noted. Conclusion: For spiral and oblique fracture patterns, simulated weight-bearing resulted in a clinically acceptable degree of displacement. Most displacement occurred early in the test period, and the rate of displacement decreased over time. Based on this model, we offer evidence that early weight-bearing appears safe for well reduced oblique and spiral fractures, but not in multifragmented patterns that have poor bone contact. Cite this article: Bone Joint J 2021;103-B(2):294–298.